Estudio de factibilidad para la generación de energía eólica del sector Puerto Alto en el Cantón Bolívar. - Chávez Leones, Adriana María (2018)
The objective of this research was to carry out a feasibility study for the generation of wind power, for which research techniques were applied such as: observation, data analysis, topography, among others, which allowed obtaining the information required for compliance with the proposed objective, quantitative methods were used through which data was taken to determine the feasibility of the study, optimizing the resource within the indicated process, the descriptive method allowed to select the factors that intervened in the study, the inductive method was applied considering as a general aspect the wind and meteorological data of the zone, to establish the causes and factors that influence in the generation of wind power such as: speed and direction of the wind, temperatures and relative humidity. The data obtained show that the sector has the following characteristics: Altimetry fluctuates between 78 and 105 masl, with a wind orientation from N to S, UTM coordinate planimetry (X 0604891, Y 9903000), relative humidity (RH) of 85%, at an ambient temperature of 26.08ºC, the average wind speed of 5.08m / s was established. Considering these data, we proceeded to investigate the different wind turbine alternatives and select the one that best suits the aforementioned specifications, based on the most relevant aspects such as: start speed of 3.2m / s and nominal power of 15000w, was also determined the total amount required for the investigation and implementation of the proposal for the Puerto Alto sector.